Choice reaction time is not related to competition success in karate combat - Oscar Martinez de Quel; Simon J. Bennett; Enrique Lopez Adan; Augusto G. Zapico; Francisco Saucedo Morales (Asociación Española de Ciencias del Deporte, 2015)
Introduction: A thorough review of extant literature on choice reaction time (CRT) and performance in combat sports reveals much equivocality, which in part stems from comparisons of quite distinct groups of participants (e.g., athlete vs. non-athlete). Therefore, the current study was designed to determine whether choice reaction time (CRT) is a predictor of different performance levels of karate fighters. Methods: A unique cohort of 123 kumite athletes from regional to international level (including 11 world champions) and 32 control subjects with no experience of karate was studied. All participants completed a CRT test in which they responded to the appearance of a non-specific stimulus (black square in different positions on a computer screen) by pressing the appropriate key on a keyboard. Results: Multiple linear regressions on mean CRT indicated that age and sex, but not performance level, were weak significant predictors. Response accuracy was not influenced by these factors. Conclusion: Competition success in karate kumite does not depend on CRT, and thus caution should be exercised if this variable is to be used in training or talent identification.